Analisis Dampak Ekonomi Kunjungan Wisata Religi Kawasan Sekumpul Terhadap Pengembangan Ekonomi Lokal (Studi Pada Makam Guru Sekumpul, Martapura Kab. Banjar) - Nurhalisa Aulia; Noor Rahmini (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
This Research was conducted to find out how he economic impact of tourism onthe economic development of local communities and how the role of the communitytowards the existence of religius tourism. The research method used is descriptivequalitative.The results of analiysis in the study can be obtained that the direct, indirect andfollow-up economic felt by local communities. Dicert economic impacts include rentalshops, clothing stores, dining places and parking. The indirect economic impact includetransportation and lodging services. The following impacts include road access and thepotensial for the other religious tourism. The role of the community towards theexistence of religious tourism is the involvement of the community in terms of regionalcleanliness, calm and religious activities carried out long ago.